Dinamika Kepribadian Tokoh Nayla dalam Kumpulan Cerpen Saia - Elva Yusanti (Madah: Jurnal Bahasa dan Sastra, 2018)
Djenar Maesa Ayu, through Saia's short story compilation, explained the physical and sexual violence undergone by her character. The violence is generally carried out by the closest person so that it forms the dynamics of the personality of the character. In this study, the problem discussed is how the dynamics of Nayla character's personality as a result of his past. This study aims at determining the dynamics of Nayla's personality. To solve problems and achieve goals, Freud's personality dynamics theory and qualitative methods are used by applying reading and recording techniques. The results show that the dynamics of Nayla's personality consisted of the instincts of life in the form of infantile sexual narcissism and exhibitionism, the instincts of death and desire to die, and objective and neurotic anxiety. Based on the results of the study, it can be concluded that personality dynamics are found in adult and children of Nayla figures, while the factors that shape personality dynamics are family and environment